2017
DOI: 10.1186/s12868-017-0345-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the appropriate time for deep brain stimulation to achieve spatial memory improvement on the Morris water maze

Abstract: BackgroundThe possibility of using deep brain stimulation (DBS) for memory enhancement has recently been reported, but the precise underlying mechanisms of its effects remain unknown. Our previous study suggested that spatial memory improvement by medial septum (MS)-DBS may be associated with cholinergic regulation and neurogenesis. However, the affected stage of memory could not be distinguished because the stimulation was delivered during the execution of all memory processes. Therefore, this study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…Significant differences in speed were not observed among the groups, suggesting that there are no SAP-induced differences in motor function (Fig. 6e), which is consistent with our previous findings [35].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Significant differences in speed were not observed among the groups, suggesting that there are no SAP-induced differences in motor function (Fig. 6e), which is consistent with our previous findings [35].…”
Section: Discussionsupporting
confidence: 92%
“…Our data support the theory that forebrain acetylcholine affects AHN, and a selective cholinergic lesion of the BFC system induces a decrease in BrdU, EGR1, DCX, and AChE levels; therefore, these findings indicate a reduction in proliferation and neuroblast production in SGZ and a decrease in hippocampal acetylcholine activity, respectively [35]. We found that the FUS-mediated BBB opening led to an increase in BDNF, EGR1, and AHN levels, which lead to an improvement in cognitive function.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This task is based upon the premise that animals have evolved an optimal strategy to explore their environment and escape from the water with a minimum amount of effort—i.e., swimming the shortest distance possible [29]. The time it takes a rat to find a hidden platform in a water pool after previous exposure to the setup, using only available external cues, is determined as a measure of spatial memory [30]. The water maze test, as described previously with minor modifications, was used on all animals [31, 32].…”
Section: Methodsmentioning
confidence: 99%